Physiology and Pathophysiology of Oxygen Sensitivity - Robert S. Fitzgerald; Asuncion Rocher (MDPI AG, 2021)
Oxygen is an essential requirement for metabolism in mammals and many other animals. Therefore, pathways that sense a reduction in available oxygen are critical for organism survival. Higher mammals developed specialized organs to detect and respond to changes in O2 content to maintain gas homeostasis by balancing oxygen demand and supply. Here, we summarize the various oxygen sensors that have been identified in mammals (carotid body, aortic bodies, and astrocytes), by what mechanisms they detect oxygen and the cellular and molecular aspects of their function on control of respiratory and circulatory O2 transport that contribute to maintaining normal physiology. Finally, we discuss how dysregulation of oxygen availability leads to elevated signalling sensitivity in these systems and may contribute to the pathogenesis of chronic cardiovascular and respiratory diseases and many other disorders. Hence, too little oxygen, too much oxygen, and a malfunctioning sensitivity of receptors/sensors can create major pathophysiological problems for the organism.